2018
DOI: 10.1245/s10434-018-6655-7
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Surgery in Patients with Pancreatic Cancer: First Results of a Clinical Trial Using SGM-101, a Novel Carcinoembryonic Antigen-Targeting, Near-Infrared Fluorescent Agent

Abstract: BackgroundNear-infrared (NIR) fluorescence is a promising novel imaging technique that can aid in intraoperative demarcation of pancreatic cancer (PDAC) and thus increase radical resection rates. This study investigated SGM-101, a novel, fluorescent-labeled anti-carcinoembryonic antigen (CEA) antibody. The phase 1 study aimed to assess the tolerability and feasibility of intraoperative fluorescence tumor imaging using SGM-101 in patients undergoing a surgical exploration for PDAC.MethodsAt least 48 h before un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
102
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 26 publications
1
102
0
4
Order By: Relevance
“…laparoscopic ultrasound or near-infrared fluorescence imaging) should also be considered in this patient category. Preliminary results showed that CEA-targeting near-infrared fluorescence imaging is promising for intraoperative evaluation of locoregional status and detection of distant metastases and further studies defining clinical benefit are ongoing (Gutowski et al 2017, Hoogstins et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…laparoscopic ultrasound or near-infrared fluorescence imaging) should also be considered in this patient category. Preliminary results showed that CEA-targeting near-infrared fluorescence imaging is promising for intraoperative evaluation of locoregional status and detection of distant metastases and further studies defining clinical benefit are ongoing (Gutowski et al 2017, Hoogstins et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…EpCAM and CEA seem of particular interest for clinical translation given our current findings. Recently, a CEA-targeted fluorescent probe for intraoperative imaging, SGM-101, was validated in 26 patients with colorectal cancer [27] and 12 patients with pancreatic cancer [28]. Results indicated that the probe was safe and feasible for visualizing both primary adenocarcinomas and small metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Near‐infrared (NIR) fluorescence imaging techniques using tumour‐targeting tracers may aid in this respect. In recent years, fluorescence‐guided surgery has gained interest, and has been able to provide surgeons with real‐time feedback and visualization of malignant tissues. SGM‐101, a carcinoembryonic antigen (CEA)‐specific tumour‐targeted fluorescent agent, can be used for fluorescence imaging to identify malignant tissue of colorectal origin.…”
Section: Introductionmentioning
confidence: 99%